Digital library on Pain and Analgesia: Structure and Impact on Professional Competencies - R. Yoshinov, Borislav; R. Yoshinov, Radoslav; B. Koleva, Ivet (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2025)
This article presents the structure of a digital library on pain and analgesia. Authors discuss the necessity of its creation, the steps of its introduction in the educational process of the medical staff, and the impact of its application on the professional competencies of members of the pain team.
Keywords: Pain; Neuropathic Pain; Nociceptive Pain; Drug Analgesia; Physical Analgesia; Digital Library